Vitamin D deficiency in children with acute bronchiolitis: a prospective cross-sectional case- control study - Inbal Golan-Tripto; Neta Loewenthal; Asher Tal; Yotam Dizitzer; Yael Baumfeld; Aviv Goldbart (BMC, 2021)
Abstract Background 25(OH) vitamin D levels are inversely associated with respiratory infections and childhood wheezing. Objective To evaluate serum 25(OH) vitamin D levels in infants and toddlers with acute bronchiolitis, compared to subjects with non-respiratory febrile illness. Methods A prospective cross-sectional case-control study which compared serum 25(OH) vitamin D levels between infants and toddlers diagnosed with acute bronchiolitis to subjects with non-respiratory febrile illness. Multivariate logistic regression, adjusted for age, sex, ethnicity and nutrition was performed. Correlation between serum vitamin D levels and bronchiolitis severity was assessed via Modified Tal Score and length of hospital stay (LOS). Results One hundred twenty-seven patients aged < 24 months were recruited; 80 diagnosed with acute bronchiolitis and 47 patients with non- respiratory febrile illnesses. Both groups had similar demographics aside from age (median [IQR] 5 [3-9] vs. 9 [5-16] months in the bronchiolitis group compared to control group (p = 0.002)). Serum 25(OH) vitamin D levels were significantly lower in the bronchiolitis group; median [IQR] 28[18-52] vs. 50[25-79] nmol/L, respectively, (p = 0.005). Deficient vitamin D levels (< 50 nmol/L) was found more frequently in the bronchiolitis group than controls; 73% vs. 51% (p = 0.028). Multivariate logistic regression showed vitamin D deficiency was more probable in bronchiolitis patients; OR [95% CI] 3.139[1.369-7.195]. No correlation was found between serum vitamin D levels and bronchiolitis severity, which was assessed via Modified Tal Score and by length of hospital stay. Conclusion Children with acute bronchiolitis displayed significantly lower vitamin D levels than children with non-respiratory acute febrile illnesses.